The prevalence of depression symptoms and other mental disorders among patients aged 65 years and older – screening in the rural community - Kujawska-Danecka, Hanna; Nowicka-Sauer, Katarzyna; Hajduk, Adam; Wierzba, Karol; Krzemiński, Wojciech; Zdrojewski, Zbigniew (Family Medicine & Primary Care Review, 2016)
Background. Mental disorders, especially depression, are common problems among the elderly. Objectives. To determine the prevalence of symptoms of mental disorders, with emphasis on symptoms of depressive disorders, in patients aged 65 years and older. Material and methods . The study involved 93 patients (59 women, 34 men, median age 70). The Primary Care Evaluation of Mental Disorders Patient Health Questionnaire (PRIME -MD PHQ) was used for the preliminary diagnosis of mental disorders. The Patient Health Questionnaire (PHQ-9) was used to assess the severity of depressive symptoms. Results. Symptoms of mental disorders were detected in 59 patients (63.4%). Thirty six (42.3%) patients reported symptoms of depressive syndrome, 13 (14%) – symptoms of anxiety, 3 (3.2%) declared alcohol overuse. Sleep disorders were reported by 58 (62%) patients. In the group of patients who reported depressive syndrome the prevalence of somatic complaints was significantly higher. The positive correlation between the number and severity of somatic complaints and symptoms of depressive disorders was revealed. In this group sleep disorders and anxiety were also reported significantly more frequent. Among the 59 patients who presented with symptoms of mental disorders 18 (30.5%) were treated pharmacologically due to psychiatric reasons. In 18 patients (19.3%) screening revealed symptoms of posttraumatic stress disorder. Conclusions . 1. In the studied group symptoms of sleep disorders and depressive disorders were the most frequent problems. 2. The severity of symptoms of depressive disorders correlated positively with the number and severity of somatic complaints. 3. Only 1/3 of the patients presenting symptoms of mental disorders were treated with pharmacotherapy. 4. Depression screening should be carried out among the elderly who report somatic problems and sleep disorders.